In the inductive step, it needs to prove that, if\(P\left( k \right)\)is true, then\(P\left( {k + 1} \right)\)is also true.
That is, \(P\left( k \right) \to P\left( {k + 1} \right)\) is true for all positive integers k.
In the inductive hypothesis, it assumes that\(P\left( k \right)\)is true for any arbitrary positive integer\(k\).
That is,\(l_0^2 + l_1^2 + ... + l_k^2 = {l_k}{l_{k + 1}} + 2\).
Now it must have to show that\(P\left( {k + 1} \right)\)is also true.
Therefore, replacing\(k\)with\(k + 1\)in the statement
\(l_0^2 + l_1^2 + ... + l_{k + 1}^2 = l_0^2 + l_1^2 + ... + l_k^2 + l_{k + 1}^2\)
From the inductive hypothesis,\(l_0^2 + l_1^2 + ... + l_k^2 = {l_k}{l_{k + 1}} + 2\).
Therefore, it is written as:
\(\begin{aligned}{c}l_0^2 + l_1^2 + ... + l_{k + 1}^2 &= {l_k}{l_{k + 1}} + 2 + l_{k + 1}^2\\ &= {l_k}{l_{k + 1}} + l_{k + 1}^2 + 2\\ &= {l_{k + 1}}\left( {{l_k} + {l_{k + 1}}} \right) + 2\\ &= {l_{k + 1}}{l_{k + 2}} + 2\end{aligned}\)
From the above, it can see that\(P\left( {k + 1} \right)\)is also true.
Hence,\(P\left( {k + 1} \right)\)is true under the assumption that\(P\left( k \right)\)is true. This
completes the inductive step.
Hence It is proven that\(l_0^2 + l_1^2 + ... + l_n^2 = {l_n}{l_{n + 1}} + 2\).